Antibacterial activity and immunomodulatory role of a proline-rich antimicrobial peptide SpPR-AMP1 against Vibrio campbellii infection in shrimp Litopenaeus vannamei. Issue 132 (January 2023) - Rattanadilog Na Phuket, Thitiya; Charoensapsri, Walaiporn; Amparyup, Piti; Imjongjirak, Chanprapa
Abstract: Antimicrobial peptides (AMPs) constitute one of the most promising sources of natural molecules used for the design of effective antimicrobial agents alternative to antibiotics. Previously, we have showed that a crab proline-rich AMP designated as Sp PR-AMP1 is a potent AMP that exhibited antimicrobial activity against both Gram-positive and Gram-negative bacteria. Here, we demonstrated the importance of Sp PR-AMP1 peptide in treating a virulent acute hepatopancreatic necrosis disease (AHPND) Vibrio campbellii VH-639 isolate and eliciting the innate immune response to counter the AHPND infection in shrimp Litopenaeus vannamei . Sp PR-AMP1 exhibited a strong antimicrobial activity against V . campbellii VH-639 at MIC value of 0.195–0.39 μM. Scanning electron microscopy (SEM) revealed the membrane disruption potential of Sp PR-AMP1 against the V. campbellii VH-639 cells. The in vivo effect of Sp PR-AMP1 in shrimp L. vannamei was investigated and the results showed that Sp PR-AMP1 was capable of modulating the innate immune response by stimulating the expression levels of AMP transcripts in shrimp hemocytes. Moreover, treatments with Sp PR-AMP1 could promote the resistance of shrimp against V. campbellii VH-639 infection as demonstrated by a significant increase in shrimp survival rate and decrease in both the bacterial load and the expression levels of bacterial PirA and PirB toxin gene transcripts in the infected shrimp. These results suggest the potential of Sp PR-AMP1 peptide with the combined antimicrobial and immunoenhancing capabilities as promising antimicrobial agent to treat V. campbellii VH-639 causing AHPND infection in shrimp aquaculture. Highlights: Sp PR-AMP1 induced damage on cell membrane of an AHPND-causing V. campbellii VH-639. Sp PR-AMP1 modulated shrimp immunity via up-regulation the AMP gene expressions. Sp PR-AMP1 could promote the resistance to V. campbellii VH-639 infection in shrimp. Sp PR-AMP1 is a promising AMP to treat V. campbellii VH-639 in shrimp aquaculture.